A Contextual Review on the Evolution of Corporate Social Responsibility - Tan, Seng Teck; Selvamalar, Ayadurai; Chua, William (Canadian Center of Science and Education, 2019)
This article attempts the perilous tasks of reviewing corporate social responsibility. Reviewing those literatures is a notorious challenge because corporate social responsibility has developed inconsistently. Authors that insist a precise definition are often disappointed because corporate social responsibility is a relative concept. It has never assumed a stagnated role. To encaptivate this review, this article peruses corporate social responsibility from a contextual approach. It reviews the development of corporate social responsibility at every stage of its evolution by addressing three contextual conundrums. Firstly, it peruses the motivational construct at every stage of development. This provides a critical insight on why corporate social responsibility was fashioned as such by analysing them contextually. Secondly, this review examines stakeholder inclusiveness at each epoch of development. This again critically exposes the category of beneficiaries included in each stage of progress categorising the evolution of their beneficiaries. Lastly, this work examines the extent of instutionalisation of corporate social responsibility illustrating the pattern in which the concept received legal and social acclamation. By addressing these three scopes, this article hopes to protrude categorically the contextual influence on corporate social responsibility so that reader(s) might understand at a deeper level the contextual reasoning and deduction on how the concept is shaped and reshaped.